2006
DOI: 10.1159/000092935
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hemoglobin Levels Predict Response to Strontium-89 and Rhenium-186-HEDP Radionuclide Treatment for Painful Osseous Metastases in Prostate Cancer

Abstract: Objective: Retrospective comparative analysis of strontium-89 chloride (Sr89) and rhenium-186-hydroxyethylidene diphosphonate (Re186-HEDP) radionuclide treatment to find predictors of response in patients with painful metastases from hormone refractory prostate cancer. Patients and Methods: Clinical data from 60 hormone refractory PCA patients (i.e. rising PSA at castrate testosterone serum levels) was obtained. Twenty-nine were treated with Sr89, 31 were treated with Re186-HEDP for painful osseous metastasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…To the best of our knowledge, the impact of hypoxia on tumor response in patients treated by internal radiotherapy has never been directly addressed. Only the effect of Hb level on global symptoms, i.e., pain or cumulative survival, was reported in the treatment for painful osseous metastases in prostate cancer with 186 Re-hydroxyethylidene-diphosphonate and 89 Sr [19,20]. The demonstration of a significant impact of anemia on tumor response in internal radiotherapy should allow improvements by considering strategies under intensive development in EBRT [21-26] but, as of today, totally ignored in internal radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the impact of hypoxia on tumor response in patients treated by internal radiotherapy has never been directly addressed. Only the effect of Hb level on global symptoms, i.e., pain or cumulative survival, was reported in the treatment for painful osseous metastases in prostate cancer with 186 Re-hydroxyethylidene-diphosphonate and 89 Sr [19,20]. The demonstration of a significant impact of anemia on tumor response in internal radiotherapy should allow improvements by considering strategies under intensive development in EBRT [21-26] but, as of today, totally ignored in internal radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This finding could explain why a better response is seen in patients who have received higher doses (19)(20)(21). On the other hand, it might be a reasonable justification for a good response in patients with few metastatic lesions treated with a lower administered activity (22)(23)(24).…”
Section: Discussionmentioning
confidence: 96%
“…Patient showed complete response to therapy and flare reaction after receiving 2,960 MBq of 186 Re-HEDP. bone markers, hemoglobin level, and previous treatments (14,23,24,36), but highly controversial issues remain. Although several studies have demonstrated that earlier treatment in patients in better clinical condition may improve the response rate (22)(23)(24), unfortunately radionuclide therapy is underutilized in Iran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report [46] suggested a relationship between serum haemoglobin levels and the chances of response to strontium-89 and rhenium-186. Recent trials suggested increased benefit in terms of pain palliation by using a combination of a radiopharmaceutical agent with chemotherapy [47,48] or bisphosphonates [49 ,50].…”
Section: Radioisotopesmentioning
confidence: 99%